Diagnostic Value of Computer Intragastric pH-metry in Children with Syndrome of Functional Dyspepsia - T.O. Kryuchko; I.N. Nesina; M.O. Rumyantseva (Zaslavsky O.Yu., 2012)
The article elaborated the indications for use in clinical practice of low-invasive express-method of intragastric pH-metry in children, that enables to diagnose acidic and antacid functions of stomach at functional dyspepsia, and in future to use this method as indicator of efficiency of antisecretory therapy and stratification of the differentiated guidelines in terms of correction of secretory violations at functional dyspepsia in children.